Penerapan Analisis Keranjang Belanja Pasar untuk Manajemen Ketersediaan Stok dalam Ekonomi Industri: Mengantisipasi Perubahan Tren - Meylaffena Fernanda; Ririt Iriani Sri Setiawati; Mohammad Wahed (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aim to explore the feasibility of Market Shopping Chart Analysis as a tool to improve stock availability management in the fashion industry. In this research, a literary study with a qualitative approach was used. Research findings reveal challenges in inventory accuracy, complexity of demand forecasting, and technology integration limitations that fashion companies face. Warehouse managers emphasize the mismatch between electronic records and actual inventory count, which hinders efficient stock management. The marketing team highlight the complexity of correctly predicting market trends and the challenges of translating insight into inventory strategies due to delays in information dissemination. Additionally, financial executive and supply chain managers emphasized the need for technology integration for efficient inventory management, but noted resource limitation affecting technological progress. These findings highlight the need for comprehensive research and strategies to address these challenges, emphasizing the potential of Market Shopping Chart Analysis as a fundamental step in redefining inventory management practices in the fashion industry.